Economic and Financial Implications of the Pharmaceutical Industry in Romania - Minculete (Piko), Georgiana Daniela; Balteș, Nicolae (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
In the wake of the financial crisis, most industries witnessed an economic downturn also boosted by the austerity measures imposed by the state. The pharmaceutical sector is one of the few sectors that followed an upward trend. Although the economic and financial crisis has long taken hold of the entire world, the domino theory did not apply to this industry; instead, the "butterfly effect" became evident. The phrase refers to the fact that the wings of a butterfly create small changes that may finally alter the route of certain elements. In the pharmaceutical industry, minor changes in research and development finally led to spectacular innovations. At present, there are no such big investments in research and development in Romania as there are in Europe; yet, due to mergers and acquisitions between Romanian and foreign companies, the pharmaceutical sector in Romania significantly contributes to the creation of added value in terms of economic development. The added value of the pharmaceutical industry in our country has increased significantly in recent years.The purpose of this article is to highlight the financial and economic significance of the pharmaceutical industry in Romania. This industry is one with an average degree of concentration; thus, the average liquidity and solvency indicators in this sector were calculated with a view to emphasizing its financial independence. The findings of this research indicate a high level of financial independence in this industry, as pharmaceutical companies are able to meet payment deadlines. This study highlights the importance of such an industry in times of economic crisis, the financial stability of the pharmaceutical sector reinforcing the need for massive investment in research and development.